Solution Priority of the Problems in the Implemantation of Zakat Financial Statement Accountability: ANP Approach - Sri Rahayu; Asmuni Asmuni; Marliyah Marliyah (Budapest International Research and Critics University, 2022)
Accountability is a good Governance principle that must be realized, preparing a report of accountability at the time and in an appropriate manner by the trustee to account, report, and disclose the results of the activities that have been carried out to the trustee who has the right and authority to hold those activities accountable. Badan Amil Zakat Nasional (BAZNAS) as the manager of zakat funds must always report the activities of collecting and disbursing funds to gain public trust, therefore it must have a financial report that is a reflection of good financial management by following under the regulation of zakat management UU No. 23 of 2011. This research aims to analyze the priority of problems and solutions to the implementation of financial accountability that needs to be reviewed by BAZNAS in North Sumatra in-depth to increase public trust. This type of research is a qualitative research that is transformed into quantitative research with the ANP method that uses super decision software. The data used is the primary data obtained from interviews with seven informants consisting of Sharia financial experts, practitioners, and academics who have an understanding of the issues discussed. The results of this study show that the priority of the problem in the implementation of financial accountability is the issue of internal audit. The priority of solutions in the implementation of financial accountability is human resources.